The Servier oncology pipeline in 2017. (July 2017) - Therasse, Patrick; Perron, Beatrice; Novack, Sarah A; Abastado, Jean-Pierre
Cancer is a complex, multifactorial disease that for years has been the focus of intensive research efforts to explore both the molecular and biological mechanisms involved and the development of novel agents to target these pathways. Servier is an independent French pharmaceutical company with a focus on oncology. Currently, Servier's commercial portfolio includes agents used to treat non-Hodgkin's lymphoma and metastatic colorectal cancer; Servier's oncology pipeline involves agents for the treatment of both solid and hematological tumors. The main areas of future research focus on the development of therapeutics targeting apoptosis or the active immune components involved in tumour development/maintenance. Servier intends to continue its focus on cutting-edge oncology innovation by collaborating with both industry and academia, and maintaining its strong patient-centered approach.